Preemptive analgesic effect of lidocaine in a chronic neuropathic pain model - Batista,Leonardo M. (2009)
Preemptive analgesia inhibits the progression of pain caused by surgical lesions. To analyze the effect of lidocaine on postoperative pain relief, we performed compression of the right sciatic nerve in Wistar rats and observed the differences on behavior between the group that received lidocaine and the group that was not treated with the local anesthetics pre-operatively. Group 1 was not operated (control); group 2 underwent the sciatic nerve ligature without lidocaine; group 3, underwent surgery with previous local infiltration of lidocaine. Group 2 showed significantly longer scratching times with a peak on day 14 post-operative (p=0.0005) and reduction in the latency to both noxious (p=0.003) and non-noxious (p=0.004) thermal stimulus. Group 3 presented significantly shorter scratching times (p=0.004) and longer latency times when compared to Group 2. Preemptive use of lidocaine 2% can potentially reduce the postoperative neuropathic pain associated with sciatic nerve compression.